Interface synergistic high-thermal-conductivity acrylic pressure-sensitive adhesive as well as preparation method and application thereof
Patent Information
- Application Number
- CN202611212590.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-11
- Publication Date
- 2026-11-03
AI Technical Summary
In existing thermally conductive acrylic pressure-sensitive adhesive systems, the filler interface compatibility is poor, the interface thermal resistance is high, the thermal conductivity and adhesion properties are difficult to coordinate, and the long-term service stability is insufficient, which cannot meet the comprehensive performance requirements of thermal interface materials in the high-end electronics and power battery fields.
By introducing borate-silica sol modification on the surface of hexagonal boron nitride, BO-Si covalent bonds are formed and a continuous silica shell is coated. Phosphate ester side groups are introduced by copolymerization of phosphate methacrylate to construct BOP coordination bonds and multiple hydrogen bonding. Combined with gradient curing process, strong chemical bonding and uniform dispersion of filler and resin matrix are achieved.
Significantly reduces interfacial thermal resistance, simultaneously improves thermal conductivity and adhesion performance, ensures long-term service stability, and is suitable for scenarios such as heat dissipation of power battery components, thermal conductivity of electronic chips and heat sink interfaces, and bonding of LED beads to aluminum substrates.
Smart Images

Figure CN123026992A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of adhesive technology, and in particular to an interface-synergistic high thermal conductivity acrylic pressure-sensitive adhesive, its preparation method, and its application. Background Technology
[0002] With the rapid development of the electronics and information industry and the new energy industry, electronic devices are continuously evolving towards higher integration and higher power density, and power battery systems are also placing more stringent requirements on heat dissipation performance. Thermal interface materials, as core functional materials filling the space between heat-generating devices and heat dissipation structures, can effectively eliminate interfacial air and reduce contact thermal resistance, making them a key component in ensuring equipment operational stability and service life. Among them, acrylic pressure-sensitive adhesives are widely used in electronic assembly, power battery pack bonding and heat dissipation due to their excellent adhesion, good weather resistance, ease of application, and cost control; however, pure acrylic resin has an extremely low intrinsic thermal conductivity of only about 0.2 W / (m²). K) is insufficient to meet the heat dissipation requirements of high-power devices, and high thermal conductivity fillers are usually introduced to construct thermal conduction paths to improve the thermal conductivity of the system.
[0003] Hexagonal boron nitride (h-BN) is one of the most commonly used sheet-like thermally conductive fillers in thermally conductive pressure-sensitive adhesive systems due to its high in-plane thermal conductivity, excellent electrical insulation, good chemical stability, and temperature resistance. However, hexagonal boron nitride has a chemically inert surface and low surface energy, resulting in extremely poor interfacial compatibility with polar acrylic resin matrices. At high filler concentrations, it is prone to agglomeration and stacking, which not only leads to a significant decrease in the adhesive and mechanical properties of the pressure-sensitive adhesive but also introduces a large amount of interfacial thermal resistance at the filler-matrix interface. This severely restricts the improvement of thermal conductivity, creating an inherent performance trade-off where "improved thermal conductivity leads to decreased adhesive performance," making it difficult to achieve synergistic optimization of the two.
[0004] To address the aforementioned issues, existing technologies primarily employ surface modification methods to improve the interfacial compatibility between boron nitride and the resin matrix. Common approaches include surface hydroxylation, silane coupling agent grafting, and polymer coating. However, simple hydroxylation only introduces a limited number of active sites on the boron nitride surface, resulting in weak interfacial bonding and an inability to effectively reduce interfacial thermal resistance. Silane coupling agent modification involves cumbersome processes and stringent reaction conditions, and the organic layer of the coupling agent itself introduces additional interfacial thermal resistance, limiting its effectiveness under high filler loading. Physical coating methods produce shells with weak adhesion to the boron nitride substrate, leading to shell detachment during long-term service and loss of interfacial modification effects. Furthermore, existing modification systems often focus solely on improving filler dispersion without designing directional chemical bonding between the filler and the resin matrix. This fails to fundamentally eliminate interfacial thermal resistance and mitigate the degradation of adhesion performance under high filler loading, failing to overcome the technical bottleneck of the trade-off between thermal conductivity and adhesion. Consequently, they are ill-suited to the comprehensive performance requirements of high thermal conductivity, high adhesion, and high stability required in high-end electronics and power battery fields.
[0005] In summary, existing thermally conductive acrylic pressure-sensitive adhesive systems still suffer from common technical problems such as poor filler interfacial compatibility, high interfacial thermal resistance, difficulty in synergistically improving thermal conductivity and adhesion, and insufficient long-term service stability. Developing novel thermally conductive pressure-sensitive adhesives that combine high interfacial bonding strength, low interfacial thermal resistance, and simultaneous improvement in thermal conductivity and adhesion is a key technical problem that urgently needs to be solved in the field of thermally conductive interface materials. Summary of the Invention
[0006] This invention provides an interface-synergistic high thermal conductivity acrylic pressure-sensitive adhesive, its preparation method, and its application. It can solve the common problems in the existing thermally conductive acrylic pressure-sensitive adhesive system, such as poor filler interface compatibility, high interface thermal resistance, difficulty in synergizing thermal conductivity and adhesion performance, and insufficient long-term service stability.
[0007] The objective of this invention can be achieved through the following technical solutions: In a first aspect, the present invention provides a method for preparing an interface-synergistic high thermal conductivity acrylic pressure-sensitive adhesive, comprising the following steps: S1. Disperse hexagonal boron nitride in an aqueous boric acid solution, add nano-silica sol, wash, and dry to obtain boric acid-silica sol modified boron nitride; In the above steps, boric acid binds to the active sites at the edges of hexagonal boron nitride via Lewis acid-base interactions, introducing high-density boron hydroxyl (B-OH) active groups. Subsequently, nano-silica sol is added, where hydroxylated silica nanoparticles undergo dehydration condensation with the boron hydroxyl groups on the boron nitride surface, forming BO-Si covalent bonds. This anchors a continuous and uniform nano-silica shell on the boron nitride surface. The BO-Si covalent bonds firmly anchor the silica sol shell to the boron nitride surface, fundamentally solving the core defects of strong surface inertness and easy detachment of the modified layer in boron nitride. Simultaneously, the silica shell introduces numerous active hydroxyl sites, mitigating the hard agglomeration effect between boron nitride layers and significantly improving the uniformity of filler dispersion in the resin matrix, providing ample interfacial reaction sites for subsequent chemical bonding with the resin matrix.
[0008] S2. Mix the soft monomer, hard monomer, and functional monomer with phosphate methacrylate to obtain a comonomer, add an initiator to carry out a copolymerization reaction, and obtain an acrylic copolymer resin. In the above steps, the acrylate soft monomer, hard monomer, functional monomer, and phosphate methacrylate undergo a free radical copolymerization reaction under the action of an initiator. The polymerizable double bonds in the phosphate methacrylate molecule participate in the copolymerization, introducing the phosphate groups of its side chains into the acrylic copolymer molecular chain, forming an acrylic resin with reactive phosphate groups on the side chains. The introduction of the phosphate ester side groups provides directional chemical bonding capability to the filler-resin interface. These phosphate groups can form BOP coordination bonds and multiple hydrogen bonds with the boron hydroxyl and silanol hydroxyl groups on the surface of the modified boron nitride filler in S1, constructing a strongly chemically bonded filler-matrix interface, significantly reducing interfacial thermal resistance, ensuring efficient phonon transmission at the interface, and simultaneously imparting good pressure-sensitive adhesion to the resin matrix through the control of the soft and hard monomer ratio.
[0009] S3. The boric acid-silica sol-modified boron nitride obtained in S1 is dispersed in the acrylic copolymer resin obtained in S2. Then, a crosslinking agent is added and stirred to mix. After coating and heat curing, a high thermal conductivity acrylic pressure-sensitive adhesive is obtained.
[0010] In the above steps, the modified boron nitride filler obtained in S1 is dispersed in the acrylic resin containing phosphate ester side groups obtained in S2. The boron hydroxyl groups remaining on the filler surface and the phosphate groups of the resin side chains form a BOP coordination bond and hydrogen bond network through a coordination curing process. During the thermosetting process, the crosslinking agent undergoes a covalent crosslinking reaction with the hydroxyl and carboxyl groups of the resin side chains to form a three-dimensional acrylate network structure, ultimately forming a composite structure of a strong filler-matrix interface and a crosslinked network. The coordination curing and gradient curing processes ensure the full formation of the interface, enabling the boron nitride sheets to form a highly efficient and interconnected thermally conductive pathway under strong interfacial bonding. At the same time, the strong interfacial bonding effectively transfers stress, avoiding the attenuation of the pressure-sensitive adhesive's bonding performance under high filler conditions. This overcomes the inherent contradiction of the traditional system where thermal conductivity and adhesion are mutually exclusive, ultimately achieving a simultaneous improvement in both thermal conductivity and adhesion performance.
[0011] Further, in step S1, the mass fraction of the boric acid aqueous solution is 5wt% to 15wt%; and the mass of pure boric acid solid added is 10% to 35% of the mass of hexagonal boron nitride. Within this range, the concentration of the boric acid solution and the amount of material added work together to ensure that the surface of the boron nitride receives sufficient and uniform grafting of boron hydroxyl groups. If the concentration is too low or the amount of material added is insufficient, there will be too few active sites and poor modification effect; if the concentration is too high or the amount of material added is too large, it will cause waste of raw materials and difficulty in washing.
[0012] Furthermore, in step S1, the diameter of the hexagonal boron nitride sheet is 5–20 μm. This diameter range ensures that the boron nitride sheet has a sufficient aspect ratio in the resin to construct an efficient heat conduction path, while avoiding scratches caused by an excessively large sheet diameter during coating or interruption of the heat conduction path due to an excessively small sheet diameter.
[0013] Furthermore, in step S1, the average particle size of silica in the nano-silica sol is 15–50 nm, and the solid content is 20%–30%. This particle size range ensures that the silica nanoparticles can form a continuous and uniform shell on the boron nitride surface without self-aggregation, and the moderate solid content ensures that the silica sol has sufficient reactivity while facilitating the washing and removal of excess silica species.
[0014] Further, in step S1, the amount of nano-silica sol added is 5% to 20% of the mass of hexagonal boron nitride based on the mass of silica. Within this range, silica can form a complete coating layer on the surface of boron nitride without excessive agglomeration. If the amount added is too low, the shell layer will be discontinuous; if it is too high, the shell layer will be too thick, introducing additional interfacial thermal resistance.
[0015] Further, in step S2, based on a total comonomer mass of 100 parts by mass, the mass parts of each comonomer are: 57-87 parts of soft acrylate monomer, 10-30 parts of hard monomer, 2-8 parts of functional monomer, and 1-6 parts of phosphate methacrylate, with the sum of the four being 100. This formulation ensures that the resin matrix simultaneously possesses good pressure-sensitive adhesion (provided by the soft monomer), cohesive strength (provided by the hard monomer), crosslinking reaction sites (provided by the functional monomer), and interfacial bonding ability (provided by the phosphate methacrylate). These four factors work synergistically to give the pressure-sensitive adhesive both high adhesion and interfacial activity.
[0016] Further, in step S2, the acrylate soft monomer is one or more of butyl acrylate, isooctyl acrylate, and ethyl acrylate. These soft monomers all have low glass transition temperatures and good flexibility, providing suitable initial tack and wetting properties for the pressure-sensitive adhesive, allowing the adhesive layer to fully wet the surface of the adhered object when pressure is applied.
[0017] Further, in step S2, the hard monomer is one or more of methyl methacrylate, vinyl acetate, and styrene. These hard monomers can increase the glass transition temperature and cohesive strength of the copolymer, enhance the tack and temperature resistance of the pressure-sensitive adhesive, and prevent creep slippage of the adhesive layer under high-temperature service conditions.
[0018] Further, in step S2, the functional monomer is one or more of acrylic acid, methacrylic acid, hydroxyethyl acrylate, and hydroxypropyl acrylate. The introduction of carboxyl or hydroxyl polar groups into these functional monomers not only provides crosslinking reaction sites for curing with the isocyanate / epoxy crosslinking agent, but also enhances the interfacial adhesion of the resin to the bonded surfaces such as metals and ceramics.
[0019] Further, in step S2, the initiator is azobisisobutyronitrile or benzoyl peroxide, and the amount of initiator is 0.3% to 0.9% of the total mass of the comonomer. This type and range of initiator ensures the smooth progress of the free radical copolymerization reaction. Too little initiator leads to incomplete polymerization and excessively large molecular weight, while too much initiator results in a violent reaction and a wide molecular weight distribution, affecting the uniformity of resin properties.
[0020] Furthermore, in step S2, the copolymerization reaction is carried out in the presence of a solvent, namely ethyl acetate, which accounts for 48% to 65% of the total mass of the comonomer and solvent. Ethyl acetate, as a solvent, can dissolve each comonomer and the resulting copolymer, and can also be quickly evaporated and removed during the coating and curing stage. The appropriate proportion of solvent ensures that the viscosity of the polymerization system is suitable, the heat transfer is uniform, and the gelation effect is avoided.
[0021] Furthermore, in step S2, the copolymerization reaction is carried out at a temperature of 70–82°C for a time of 4.5–8 hours. Within this temperature and time range, the half-life of azobisisobutyronitrile or benzoyl peroxide is well matched with the polymerization rate, ensuring a high monomer conversion rate. If the temperature is too low or the time is too short, the reaction will be incomplete; if the temperature is too high, the molecular weight distribution will become wider.
[0022] Furthermore, in step S3, the amount of boric acid-silica sol-modified boron nitride added is 20% to 50% of the mass of the solid component of the acrylic copolymer resin obtained in step S2. Within this filler addition range, the pressure-sensitive adhesive can gradually improve its thermal conductivity while maintaining good coating processability. When the addition amount is less than 20%, the thermal conductivity path is discontinuous, and when it is more than 50%, the system viscosity is too high and the cost is too high.
[0023] Further, in step S3, the crosslinking agent is an isocyanate crosslinking agent or an epoxy crosslinking agent, and the amount of crosslinking agent is 0.5% to 2% of the solid component mass of the acrylic copolymer resin. Both isocyanate and epoxy crosslinking agents can react with the hydroxyl and carboxyl groups of the resin side chains to form a three-dimensional network. This dosage range ensures that the crosslinking density is sufficient to improve cohesive strength and heat resistance, while avoiding excessive crosslinking that would cause the adhesive layer to become brittle and reduce peel strength.
[0024] Further, in step S3, the specific steps of stirring and mixing are as follows: (1) Boric acid-silica sol modified boron nitride and ethyl acetate are mixed at a mass ratio of 1:(1~2) and stirred at 300~500 rpm for 10~15 min to obtain boric acid-silica sol modified boron nitride pre-dispersion slurry; This step involves pre-wetting and pre-dispersing the modified boron nitride with ethyl acetate solvent, which fully wets the filler surface, opens up soft agglomerates, and forms a pre-dispersed slurry with good flowability. This lays the foundation for uniform blending with the resin in the subsequent process and avoids dust and local agglomeration caused when the dry powder is directly added to the resin. (2) Add the boric acid-silica sol modified boron nitride pre-dispersion slurry to the acrylic copolymer resin in 3 to 5 batches. After each batch is added, stir at medium speed for 10 to 15 minutes at a speed of 800 to 1200 rpm and a temperature of 40 to 50°C to obtain a mixed slurry. In the above steps, the filler is added in batches, combined with medium-speed stirring and moderate heating, so that each batch of filler is fully dispersed in the resin before the next batch is introduced. This avoids the formation of hard agglomerates due to excessively high local concentrations caused by adding all at once. Mild heating at 40-50°C can reduce the viscosity of the system and promote the uniform distribution of the filler in the resin matrix. (3) Disperse the mixed slurry under ice-water bath conditions with ultrasonic power of 200-300W for 5-10 minutes, and control the system temperature to not exceed 50℃ during the dispersion process; In the above steps, the cavitation effect of ultrasound can effectively open up the soft aggregates between the layers, so that the boron nitride layers are uniformly dispersed in the resin in a monolayer or oligolayer state; the forced temperature control of the ice water bath avoids the early cross-linking of the resin or rapid evaporation of the solvent caused by the heat effect of ultrasound, thus ensuring the stability of the system. (4) After ultrasonic treatment, seal the mixed slurry and let it stand at 30-40°C for 30-60 minutes. Then add the crosslinking agent, stir at 200-300 rpm for 5-10 minutes and degas under vacuum. Then the coating and curing can be carried out.
[0025] In the above steps, static curing allows the boron hydroxyl groups on the filler surface to fully contact and oriented with the phosphate groups on the resin side chains under shear-free conditions, forming a BOP coordination pre-assembled structure; the strategy of adding the crosslinking agent after the crosslinking agent avoids premature crosslinking that hinders filler dispersion and interfacial coordination; vacuum degassing removes entrained gas in the system, ensuring that the coated film is dense and free of pinhole defects.
[0026] Furthermore, in step S3, the thermosetting process employs a three-stage gradient heating process, specifically as follows: Place the coated wet film in an oven at 60-80℃ and bake for 1-2 minutes to complete the interface pre-reaction; then raise the temperature to 100-115℃ and bake for 1-2 minutes; finally, continue to raise the temperature to 120-130℃ and bake for 30-60 seconds; throughout the curing process, control the laminar airflow velocity in the oven to 0.5-1.5 m / s to avoid direct blowing on the adhesive surface, which may cause pinholes and ripple defects.
[0027] This three-stage gradient heating process promotes the interfacial coordination and pre-assembly of boron hydroxyl groups on the filler surface and phosphate groups on the resin in the low-temperature stage; drives the covalent cross-linking reaction between the cross-linking agent and the side chain hydroxyl / carboxyl groups of the resin to build a three-dimensional network in the medium-temperature stage; and strengthens the dehydration condensation of residual hydroxyl groups at the interface to form a small number of covalent bonds and eliminate internal stress during curing in the high-temperature stage. The temperature windows of the three types of reactions—interfacial coordination, resin cross-linking, and interface strengthening—are precisely matched step by step. At the same time, gentle exhaust is carried out at a laminar flow velocity of 0.5 to 1.5 m / s to avoid pinhole and ripple defects caused by direct blowing on the adhesive surface. Finally, a high-performance pressure-sensitive adhesive film with strong filler-matrix interfacial bonding, uniform cross-linking network, and smooth and defect-free surface is obtained.
[0028] Secondly, the present invention provides an interface-synergistic high thermal conductivity acrylic pressure-sensitive adhesive, which is prepared by the method described above for preparing the interface-synergistic high thermal conductivity acrylic pressure-sensitive adhesive.
[0029] Thirdly, this invention provides an application of an interface-synergistic high thermal conductivity acrylic pressure-sensitive adhesive in the heat dissipation bonding of power battery components, the interface thermal conductivity between electronic chips and heat sinks, the bonding of LED beads to aluminum substrates, and the thermal interface assembly of 5G power devices.
[0030] The beneficial effects of this invention are: 1. This invention achieves integrated synergy between modified boron nitride filler and acrylic resin matrix through a three-step synergistic interfacial chemical bonding design: In S1, boric acid introduces high-density boron hydroxyl active sites onto the surface of inert boron nitride, and then anchors a continuous and uniform silica sol shell layer through in-situ hydrolysis with BO-Si covalent bonds, fundamentally solving the defects of strong inertness and easy detachment of modified layer on the boron nitride surface. At the same time, the silica shell layer alleviates the hard agglomeration of the sheets and improves the dispersion uniformity; S2 introduces phosphate methacrylate copolymer into the acrylic resin containing phosphate ester side groups, making the filler surface... The boron hydroxyl groups on the surface form BOP coordination bonds and multiple hydrogen bonds with the phosphate groups on the resin side chains, constructing a strongly chemically bonded filler-matrix interface, which significantly reduces interfacial thermal resistance and ensures efficient phonon transmission. The coordination curing and gradient curing process in S3 ensures the full formation of interfacial interactions, enabling the boron nitride sheets to form highly efficient and interconnected thermally conductive pathways under strong interfacial bonding. At the same time, the strong interfacial bonding effectively transfers stress and avoids the attenuation of adhesive performance under high filling conditions, breaking through the inherent contradiction of the traditional system where thermal conductivity and adhesive performance are mutually exclusive, and ultimately achieving a simultaneous improvement in thermal conductivity and adhesive performance.
[0031] 2. This invention significantly improves the interfacial bonding between the filler and the resin matrix through a composite modification of hexagonal boron nitride by boric acid activation and in-situ silica sol coating. A continuous and uniform silica shell is anchored on the boron nitride surface by BO-Si covalent bonds, introducing high-density active hydroxyl sites while avoiding the problem of easy detachment of the physical coating layer. Combined with the directional coordination of the phosphate ester groups on the resin side chains, a strong bonding interface with low interfacial thermal resistance is constructed, effectively eliminating phonon scattering at the filler-matrix interface. This lays the structural foundation for the synergistic improvement of thermal conductivity and adhesion under high filler conditions.
[0032] 3. This invention introduces phosphate methacrylate comonomer into the acrylic resin molecular chain, providing directional chemical bonding capability at the filler-matrix interface. The phosphate groups can form BOP coordination bonds and multiple hydrogen bonds with the boron hydroxyl and silanol hydroxyl groups on the filler surface, resulting in a strongly chemically bonded interfacial bond between the filler and the resin. When the resin side chains do not contain phosphate groups, the interfacial bonding relies solely on physical adsorption and hydrogen bonding, leading to high interfacial thermal resistance and low stress transfer efficiency. However, this invention, by controlling the copolymerization ratio of phosphate methacrylate, achieves simultaneous increases in peel strength and thermal conductivity, fully demonstrating the enhancing effect of BOP coordination bonds on interfacial bonding.
[0033] 4. The pressure-sensitive adhesive of this invention achieves simultaneous improvement in thermal conductivity and adhesion through interfacial chemical bonding design, breaking the traditional performance trade-off between increased thermal conductivity and decreased adhesion in thermally conductive pressure-sensitive adhesives. Strong interfacial bonding ensures efficient connectivity of the thermal conductivity pathway, while interfacial chemical bonding effectively transfers stress, mitigating the negative impact of high filler content on the adhesive performance. All embodiments exhibit tackiness exceeding 72 hours, with no residue after high-temperature aging and high performance retention, while maintaining excellent electrical insulation properties. The adhesive film has a smooth, defect-free appearance and is suitable for various applications such as power battery components, electronic chip heat dissipation, LED bead bonding, and 5G power device thermal interface assembly. Its overall performance surpasses existing thermally conductive pressure-sensitive adhesive products. Attached Figure Description
[0034] Figure 1 This is a field emission scanning electron microscope image of borate-silica sol-modified hexagonal boron nitride prepared in Example 1 of this invention; Figure 2 The infrared spectrum of the acrylic copolymer resin prepared in Example 1 of this invention; Figure 3 Field emission scanning electron microscope (FESEM) images of the cross sections of the acrylic pressure-sensitive adhesives obtained in Comparative Examples 1, 2, and 1 of the present invention are shown below; wherein, (a) represents the FESEM image of the acrylic pressure-sensitive adhesive obtained in Comparative Example 1 of the present invention; (b) represents the FESEM image of the acrylic pressure-sensitive adhesive obtained in Comparative Example 2 of the present invention; and (c) represents the FESEM image of the acrylic pressure-sensitive adhesive obtained in Example 1 of the present invention. Figure 4 This is a photograph of the acrylic pressure-sensitive adhesive prepared in Example 1 of the present invention. Detailed Implementation
[0035] The specific embodiments of the present invention will be described in detail below, but it should be understood that the scope of protection of the present invention is not limited to the specific embodiments.
[0036] Example 1 This embodiment provides a method for preparing an interface-synergistic high thermal conductivity acrylic pressure-sensitive adhesive, including the following steps: S1. Preparation of boric acid-silica sol modified boron nitride filler: A 5 wt% boric acid aqueous solution was prepared, and the mass of pure boric acid solid added was 10% of the mass of hexagonal boron nitride. Hexagonal boron nitride with a particle size of 10 μm was added, and the mixture was heated and activated at 60 °C for 6 h. After activation, the mixture was centrifuged and washed with deionized water until the pH of the filtrate was 7.0, and then redispersed in deionized water. Nano-silica sol was added, with an average silica particle size of 20 nm and a solid content of 25%. The amount of nano-silica sol added was 5% of the mass of hexagonal boron nitride based on the mass of silica. The mixture was hydrolyzed in situ at 80 °C for 3 h. The product was centrifuged, washed, and vacuum dried at 80 °C for 12 h to obtain boric acid-silica sol modified boron nitride filler. Figure 1 The image shows a field emission scanning electron microscope (FESEM) image of boron nitride filler modified with boric acid-silica sol. It is clearly visible that a continuous layer of nano-silica particles is uniformly coated on the surface of the hexagonal boron nitride sheets, forming a core-shell composite structure. The silica particles are anchored to the boron nitride surface through in-situ hydrolysis, with no obvious free particles or detachment. This demonstrates that the silica sol shell and the boron nitride substrate are firmly bonded through BO-Si covalent bonds, significantly improving surface roughness and providing sufficient active sites for subsequent interfacial bonding with the resin matrix.
[0037] S2. Synthesis of acrylic resin containing phosphate ester side groups: Using 100 parts by mass of comonomers, 70 parts of isooctyl acrylate, 20 parts of methyl methacrylate, 5 parts of hydroxyethyl acrylate, and 5 parts of phosphate methacrylate were mixed evenly to obtain comonomers. Using ethyl acetate as solvent (solvent accounting for 60% of the total mass of comonomers and solvent), 0.5% of azobisisobutyronitrile initiator (based on the total mass of comonomers) was added. Solution polymerization was carried out at 75°C for 6 hours to obtain an acrylic copolymer resin with a solid content of approximately 40%. Figure 2 The infrared spectrum of the acrylic copolymer resin is shown, with the following result: 3250 cm⁻¹ -1 The characteristic peak of the stretching vibration corresponding to the superposition of hydroxyl and carboxyl groups is 1730 cm⁻¹. -1 1160cm -1 The peak at 980 cm⁻¹ is a characteristic absorption peak of the ester carbonyl group and COC bond in the acrylate structure. -1 The presence of a characteristic absorption peak for POC bonds indicates that phosphate methacrylate has successfully participated in copolymerization and incorporated into the side chains of the copolymer molecules, and the structure of the resin functional groups is consistent with the design.
[0038] S3. Preparation of pressure-sensitive adhesive: The amount of boric acid-silica sol-modified boron nitride added is 20% of the mass of the solid component of the acrylic copolymer resin obtained in step S2; first, the boric acid-silica sol-modified boron nitride and ethyl acetate are mixed at a mass ratio of 1:1.5 and stirred at 300 rpm for 15 min to obtain a pre-dispersed slurry; it is added to the acrylic copolymer resin in 3 batches, and stirred at 800 rpm and 40℃ for 15 min after each batch is added; after the blending is completed, it is ultrasonically dispersed at 200W in an ice-water bath for 10 min, and the system temperature is controlled not to exceed 50℃; after sealing, it is allowed to stand at 30℃ for 60 min for curing; 0.5% of the mass of the solid component of the acrylic copolymer resin is added as an isophorone diisocyanate crosslinking agent, stirred at 200 rpm for 10 min and vacuum degassed; it is coated on a release film and cured by a three-stage gradient temperature rise: pre-baking at 60℃ for 2 min, crosslinking at 100℃ for 2 min, and strengthening at 120℃ for 1 min, with a wind speed of 0.5 m / s throughout the curing process, to obtain a high thermal conductivity acrylic pressure-sensitive adhesive with a thickness of 50 μm.
[0039] Figure 3 - (c) is a cross-sectional morphology image of the high thermal conductivity acrylic pressure-sensitive adhesive prepared in Example 1. The electron microscope image clearly shows that the boron nitride-modified boron nitride sheets are uniformly oriented and dispersed in the acrylic resin matrix, without obvious filler agglomeration or stacking, and without any pores or defect channels formed by filler aggregation. This phenomenon verifies that the modified boron nitride, due to surface polarity matching and interfacial chemical bonding mechanisms, has excellent compatibility with the acrylic resin matrix, solving the technical problem of easy agglomeration of traditional unmodified boron nitride, and laying a structural foundation for the construction of continuous thermal conductive pathways. Cross-sectional structural characteristics: The pressure-sensitive adhesive cross-section exhibits a dense and continuous microstructure, without pinholes, bubbles, cracks, or other preparation defects; the modified boron nitride sheets are tightly bonded to the resin matrix, with no obvious interfacial gaps, and the edges of the sheets form a smooth transition with the resin matrix, proving that a strong interfacial bond is formed between the filler and the matrix, with no obvious interfacial separation. The overlapping of the sheets forms a continuous three-dimensional thermal conductive pathway, which can effectively reduce the thermal resistance of the system and improve thermal conductivity. The correlation between microstructure and performance: The dense, defect-free internal structure and uniform filler dispersion explain, from a microscopic perspective, why this thermally conductive pressure-sensitive adhesive possesses both excellent thermal conductivity and adhesive properties. On the one hand, the uniformly overlapping boron nitride sheets form an efficient phonon transport pathway, which, combined with a strong bonding interface with low interfacial thermal resistance, enables rapid heat conduction. On the other hand, the strong interfacial bonding between the filler and the resin effectively transfers stress, preventing a decrease in cohesive strength and adhesive properties under high filler conditions, thus ensuring the adhesive properties and mechanical stability of the pressure-sensitive adhesive.
[0040] Figure 4The image shows a photograph of the high thermal conductivity acrylic pressure-sensitive adhesive prepared in Example 1. As can be seen from the image, the modified boron nitride filler is uniformly dispersed in the acrylic resin system. The slurry has a uniform color and no obvious powder agglomeration, stratification, or sedimentation. The slurry dispersion is stable and has good coating and processing performance.
[0041] Example 2 This embodiment provides a method for preparing an interface-synergistic high thermal conductivity acrylic pressure-sensitive adhesive, including the following steps: S1. Preparation of boric acid-silica sol modified boron nitride filler: Prepare an 8wt% boric acid aqueous solution, add pure boric acid solid at 18% of the mass of hexagonal boron nitride, add hexagonal boron nitride with a particle size of 5μm, and heat at 70℃ for 5h for activation treatment; after activation, centrifuge and wash with deionized water until the pH of the filtrate is 7.2, and redisperse in deionized water; add nano-silica sol, the average particle size of silica in the nano-silica sol is 15nm and the solid content is 25%, the amount of nano-silica sol added is 10% of the mass of hexagonal boron nitride based on the mass of silica, and perform in-situ hydrolysis reaction at 85℃ for 2.5h; the product is centrifuged and washed, and vacuum dried at 85℃ for 10h to obtain boric acid-silica sol modified boron nitride filler.
[0042] S2. Synthesis of acrylic resin containing phosphate ester side groups: With a total comonomer mass of 100 parts by mass, 65 parts of butyl acrylate, 25 parts of vinyl acetate, 4 parts of acrylic acid, and 6 parts of phosphate methacrylate were mixed evenly to obtain the comonomer; using ethyl acetate as solvent, with the solvent accounting for 55% of the total mass of the comonomer and solvent, 0.6% of azobisisobutyronitrile initiator accounting for the total mass of the comonomer was added, and solution polymerization was carried out at 78°C for 5.5 h to obtain acrylic copolymer resin with a solid content of about 45%.
[0043] S3. Preparation of pressure-sensitive adhesive: The amount of boric acid-silica sol-modified boron nitride added is 30% of the mass of the solid component of the acrylic copolymer resin obtained in step S2; first, boric acid-silica sol-modified boron nitride and ethyl acetate are mixed at a mass ratio of 1:1.2 and stirred at 400 rpm for 12 min to obtain a pre-dispersion slurry; it is added to the acrylic copolymer resin in 4 batches, and stirred at 1000 rpm and 45℃ for 12 min after each batch is added; after the blending is completed, it is ultrasonically dispersed at 250W in an ice water bath for 8 min, and controlled... The system temperature should not exceed 50℃; after sealing, it should be allowed to stand at 35℃ for 45 minutes for curing; add isophorone diisocyanate crosslinking agent accounting for 1% of the solid component of acrylic copolymer resin, stir at 250 rpm for 8 minutes and degas under vacuum; coat it on the release film, and use a three-stage gradient temperature rise curing: pre-baking at 70℃ for 1.5 minutes, crosslinking at 105℃ for 1.5 minutes, and strengthening at 125℃ for 45 seconds, with a wind speed of 1.0 m / s throughout the curing process, to obtain a high thermal conductivity acrylic pressure-sensitive adhesive with a thickness of 50 μm.
[0044] Example 3 This embodiment provides a method for preparing an interface-synergistic high thermal conductivity acrylic pressure-sensitive adhesive, including the following steps: S1. Preparation of boric acid-silica sol modified boron nitride filler: A 10wt% boric acid aqueous solution was prepared, and the mass of pure boric acid solid added was 25% of the mass of hexagonal boron nitride. Hexagonal boron nitride with a particle size of 15μm was added, and the mixture was heated and activated at 80℃ for 4h. After activation, the mixture was centrifuged and washed with deionized water until the pH of the filtrate was 6.8, and then redispersed in deionized water. Nano-silica sol was added, with an average silica particle size of 30nm and a solid content of 20%. The amount of nano-silica sol added was 15% of the mass of hexagonal boron nitride based on the mass of silica. The mixture was hydrolyzed in situ at 90℃ for 2h. The product was centrifuged, washed, and vacuum dried at 90℃ for 8h to obtain boric acid-silica sol modified boron nitride filler.
[0045] S2. Synthesis of acrylic resin containing phosphate ester side groups: With a total comonomer mass of 100 parts by mass, take 60 parts of ethyl acrylate, 28 parts of styrene, 7 parts of hydroxypropyl acrylate, and 5 parts of phosphate methacrylate and mix them evenly to obtain the comonomer; using ethyl acetate as solvent, with the solvent accounting for 50% of the total mass of the comonomer and solvent, add 0.8% of benzoyl peroxide initiator accounting for the total mass of the comonomer, and polymerize in solution at 80°C for 5 hours to obtain acrylic copolymer resin with a solid content of about 50%.
[0046] S3. Preparation of pressure-sensitive adhesive: The amount of boric acid-silica sol-modified boron nitride added is 40% of the mass of the solid component of the acrylic copolymer resin obtained in step S2; first, the boric acid-silica sol-modified boron nitride and ethyl acetate are mixed at a mass ratio of 1:1 and stirred at 450 rpm for 10 min to obtain a pre-dispersion slurry; it is added to the acrylic copolymer resin in 4 batches, and stirred at 1100 rpm and 45℃ for 10 min after each batch is added; after the blending is completed, it is ultrasonically dispersed at 280W for 6 min in an ice-water bath, and the system temperature is controlled not to exceed 50℃; after sealing, it is allowed to stand at 38℃ for 40 min for curing; propylene glycol diglycidyl ether is added at 1.5% of the mass of the solid component of the acrylic copolymer resin, stirred at 280 rpm for 6 min and vacuum degassed; it is coated on a release film and cured by a three-stage gradient temperature rise: pre-baking at 75℃ for 1.2 min, cross-linking at 110℃ for 1.2 min, and strengthening at 128℃ for 40 s, with a wind speed of 1.2 m / s throughout the curing process, to obtain a high thermal conductivity acrylic pressure-sensitive adhesive with a thickness of 50 μm.
[0047] Example 4 This embodiment provides a method for preparing an interface-synergistic high thermal conductivity acrylic pressure-sensitive adhesive, including the following steps: S1. Preparation of boric acid-silica sol modified boron nitride filler: A 12wt% boric acid aqueous solution was prepared, and the mass of pure boric acid solid added was 30% of the mass of hexagonal boron nitride. Hexagonal boron nitride with a particle size of 8μm was added, and the mixture was heated and activated at 85℃ for 3h. After activation, the mixture was centrifuged and washed with deionized water until the pH of the filtrate was 7.5, and then redispersed in deionized water. Nano-silica sol was added, with an average silica particle size of 40nm and a solid content of 30%. The amount of nano-silica sol added was 18% of the mass of hexagonal boron nitride based on the mass of silica. The mixture was hydrolyzed in situ at 95℃ for 1.5h. The product was centrifuged, washed, and vacuum dried at 95℃ for 6h to obtain boric acid-silica sol modified boron nitride filler.
[0048] S2. Synthesis of acrylic resin containing phosphate ester side groups: With a total comonomer mass of 100 parts by mass, 57 parts of isooctyl acrylate, 30 parts of methyl methacrylate, 8 parts of methacrylic acid, and 5 parts of phosphate methacrylate were mixed evenly to obtain the comonomer; using ethyl acetate as solvent, with the solvent accounting for 48% of the total mass of the comonomer and solvent, 0.9% of azobisisobutyronitrile initiator accounting for the total mass of the comonomer was added, and solution polymerization was carried out at 82°C for 4.5 h to obtain acrylic copolymer resin with a solid content of about 52%.
[0049] S3. Preparation of pressure-sensitive adhesive: The amount of boric acid-silica sol-modified boron nitride added is 45% of the mass of the solid component of the acrylic copolymer resin obtained in step S2; first, the modified boron nitride and ethyl acetate are mixed at a mass ratio of 1:1.8 and stirred at 480 rpm for 11 min to obtain a pre-dispersion slurry; it is added to the acrylic copolymer resin in 5 batches, and stirred at 1150 rpm and 48℃ for 11 min after each batch is added; after blending, it is ultrasonically dispersed at 300W for 5 min in an ice-water bath, and the system temperature is controlled not to exceed 50℃; after sealing, it is allowed to stand at 40℃ for 35 min for curing; 1.8% of the mass of the solid component of the acrylic copolymer resin is added as adipisocyanate trimer, stirred at 300 rpm for 5 min and vacuum degassed; it is coated on a release film and cured by a three-stage gradient temperature rise: pre-baking at 78℃ for 1 min, crosslinking at 112℃ for 1 min, and strengthening at 130℃ for 30 s, with a wind speed of 1.3 m / s throughout the curing process, to obtain a high thermal conductivity acrylic pressure-sensitive adhesive with a thickness of 50 μm.
[0050] Example 5 This embodiment provides a method for preparing an interface-synergistic high thermal conductivity acrylic pressure-sensitive adhesive, including the following steps: S1. Preparation of boric acid-silica sol modified boron nitride filler: A 15wt% boric acid aqueous solution was prepared, and the mass of pure boric acid solid added was 35% of the mass of hexagonal boron nitride. Hexagonal boron nitride with a particle size of 20μm was added, and the mixture was heated and activated at 90℃ for 2h. After activation, the mixture was centrifuged and washed with deionized water until the pH of the filtrate was 6.5, and then redispersed in deionized water. Nano-silica sol was added, with an average silica particle size of 50nm and a solid content of 25%. The amount of nano-silica sol added was 20% of the mass of hexagonal boron nitride based on the mass of silica. The mixture was hydrolyzed in situ at 100℃ for 1h. The product was centrifuged, washed, and vacuum dried at 100℃ for 5h to obtain boric acid-silica sol modified boron nitride filler.
[0051] S2. Synthesis of acrylic resin containing phosphate ester side groups: With a total comonomer mass of 100 parts by mass, take 87 parts of butyl acrylate, 10 parts of methyl methacrylate, 2 parts of acrylic acid, and 1 part of phosphate methacrylate and mix them evenly to obtain the comonomer; use ethyl acetate as solvent, with the solvent accounting for 65% of the total mass of the comonomer and solvent, add 0.3% of benzoyl peroxide initiator accounting for the total mass of the comonomer, and polymerize in solution at 70°C for 8 hours to obtain acrylic copolymer resin with a solid content of about 35%.
[0052] S3. Preparation of pressure-sensitive adhesive: The amount of boric acid-silica sol-modified boron nitride added is 50% of the mass of the solid component of the acrylic copolymer resin obtained in step S2; first, the modified boron nitride and ethyl acetate are mixed at a mass ratio of 1:2 and stirred at 500 rpm for 10 min to obtain a pre-dispersion slurry; it is added to the acrylic copolymer resin in 5 batches, and after each batch is added, it is stirred at 1200 rpm and 50℃ for 10 min; after the blending is completed, it is ultrasonically dispersed at 300W for 5 min in an ice-water bath, and the system temperature is controlled not to exceed 50℃; after sealing, it is allowed to stand at 40℃ for 30 min for curing; 2% of the mass of the solid component of the acrylic copolymer resin is added, stirred at 300 rpm for 5 min and vacuum degassed; it is coated on a release film and cured by a three-stage gradient temperature rise: pre-baking at 80℃ for 1 min, cross-linking at 115℃ for 1 min, and strengthening at 130℃ for 30 s, with a wind speed of 1.5 m / s throughout the curing process, to obtain a high thermal conductivity acrylic pressure-sensitive adhesive with a thickness of 50 μm.
[0053] Comparative Example 1 The only difference between this comparative example and Example 1 is that the boric acid-silica sol-modified boron nitride filler is omitted. Figure 3 - (a) is a cross-sectional morphology diagram of the acrylic pressure-sensitive adhesive prepared in Comparative Example 1. As can be seen from the figure, the cross-section of the pure resin is smooth and dense, without any thermally conductive filler particles, and there is no internal thermally conductive pathway. Therefore, the overall thermal conductivity is extremely low and cannot meet the heat dissipation requirements of high-power devices.
[0054] Comparative Example 2 The only difference between this comparative example and Example 1 is that an equal amount of hexagonal boron nitride (with a sheet diameter of 10 μm) was used to replace the boron nitride-modified boron nitride filler modified with boronic acid-silica sol. Figure 3 - (b) is a cross-sectional morphology diagram of the acrylic pressure-sensitive adhesive prepared in Comparative Example 2. As can be seen from the figure, the unmodified boron nitride sheets have poor interfacial compatibility with the resin matrix, and the sheets show obvious agglomeration and stacking. There are clear interfacial gaps and separation gaps between the filler and the resin, and pore defects are visible in some areas. The interfacial thermal resistance is high, the thermal conductivity is poor, and the weak interfacial bonding leads to a decrease in adhesive performance, which confirms the inherent contradiction that the improved thermal conductivity of the unmodified system leads to a decrease in adhesiveness.
[0055] The acrylic pressure-sensitive adhesives prepared in Examples 1 to 5 and Comparative Examples 1 and 2 were subjected to performance tests. The test items are as follows: (1) Appearance inspection of the adhesive film: Place the prepared pressure-sensitive adhesive film under natural light and 40W fluorescent lamp, and visually observe whether the surface of the adhesive film is flat, whether there are particles, bubbles, pinholes, ripples and other defects, and record the transparency / semi-transparency of the adhesive film.
[0056] (2) Initial tack (GB / T 4852-2002, rolling ball method): Place the pressure-sensitive adhesive with the adhesive side facing up on an inclined test plate with an inclination angle of 30°, and let standard steel balls of different diameters roll freely from the top. Record the number of the largest steel ball that can stay on the adhesive surface for more than 5 seconds. The larger the number of the steel ball, the higher the initial tack. Each sample is tested in parallel 3 times and the average value is taken.
[0057] (3) Holding power (GB / T 4851-2014): The pressure-sensitive adhesive sample (25mm×100mm) is pasted on a stainless steel test plate with a pasting area of 25mm×25mm. It is rolled back and forth 3 times with a 2kg standard roller at a speed of about 300mm / min. After being left for 20min, it is suspended vertically with a 1kg standard weight hanging from the bottom. The time it takes for the sample to fall off the test plate is recorded (unit: h). The longer the time, the better the holding power. Each sample is tested in parallel 3 times and the average value is taken.
[0058] (4) 180° peel strength (GB / T 2792-2014): The pressure-sensitive adhesive sample (25 mm wide) is attached to a clean stainless steel plate surface and rolled back and forth 3 times with a 2 kg standard roller at a speed of about 300 mm / min. After 20 min, a 180° peel test is performed on a universal testing machine at a peel speed of 300 mm / min. The average peel force during the peel process is recorded (unit: N / 25 mm). Each sample is tested in parallel 5 times and the average value is taken.
[0059] (5) Thermal conductivity in the thickness direction (ASTM D5470, heat flow meter method): The film to be tested is cut into a circular piece with a diameter of 30 mm and placed between the upper and lower hot rods of the thermal conductivity tester. The hot end temperature is set to 50℃ and the cold end temperature is set to 20℃. After the system reaches thermal steady state, the heat flux density passing through the sample is measured by the heat flow meter. The thermal conductivity in the thickness direction (unit: W / m·K) is calculated by combining the sample thickness and the temperature difference between the upper and lower surfaces. Each sample is tested in parallel 3 times and the average value is taken.
[0060] (6) Volume resistivity (GB / T 31838.2-2019): A high-resistivity meter was used in conjunction with a three-electrode testing device. The film to be tested was placed between the cylindrical electrode and the ring electrode. A DC test voltage of 100V was applied, and the volume resistivity of the sample was read after charging for 60s. The volume resistivity (unit: Ω·cm) was calculated by combining the sample thickness and the electrode area. The test environment temperature was 23±2℃ and the relative humidity was 50±5%. Each sample was tested in parallel 3 times, and the average value was taken.
[0061] (7) Temperature resistance test: The pressure-sensitive adhesive film is attached to the surface of a clean stainless steel plate and aged in a constant temperature oven at 120℃ for 72 hours. After cooling to room temperature, the film is peeled off and the steel plate surface is observed to see if there is any residual adhesive. At the same time, the 180° peel strength of the film before and after aging is tested, and the performance retention rate is calculated (peel strength after aging / peel strength before aging × 100%).
[0062] The test results are shown in Table 1: Table 1
[0063] As shown in Table 1, in terms of the basic properties of pressure-sensitive adhesives, the adhesive films prepared in Examples 1-5 all have smooth and defect-free surfaces, and their initial tack and holding power meet the basic application requirements of pressure-sensitive adhesives, while their volume resistivity remains at 10 Ω·cm. 14 With a strength of Ω·cm or higher, it exhibits excellent electrical insulation properties. All embodiments demonstrate tackiness exceeding 72 hours, with no residue after aging at 120°C for 72 hours, high performance retention, and excellent temperature resistance.
[0064] The differences in performance between Examples 1 to 5 are mainly due to the different effects of process conditions on the surface modification effect of boron nitride, filler loading, resin phosphate content, and interfacial bonding strength in each example.
[0065] Example 1 employs low boric acid concentration and low-temperature long-term activation, resulting in a continuous and uniform shell layer with low silica sol coating. The resin system has a moderate phosphate ester content and low filler content. The resulting film exhibits optimal transparency and balanced overall performance, making it suitable for low-heat-dissipation applications where both appearance and adhesion are critical.
[0066] Example 2 increased the amount of boric acid and silica sol coating, optimized the resin monomer ratio and phosphate ester content, increased the filler content, and further improved the interfacial bonding strength. The thermal conductivity and adhesion properties were improved in a balanced manner, making it suitable for heat dissipation bonding scenarios in conventional electronic devices.
[0067] In Example 3, the amount of boron nitride modified with boric acid-silica sol was 40% of the mass of the solid component of the acrylic copolymer resin obtained in step S2. The boron nitride modification process and resin system parameters were optimally matched, the boric acid activation and silica sol coating effects were best, the coordination between the phosphate ester groups and the hydroxyl groups on the filler surface was sufficient, the interfacial thermal resistance was lowest, and the thermal conductivity pathway was efficiently constructed. An optimal balance was achieved between thermal conductivity and adhesion.
[0068] In Example 4, the amount of boric acid-silica sol-modified boron nitride added was 45% of the solid component mass of the acrylic copolymer resin obtained in step S2. Simultaneously, the amounts of boric acid and silica sol were increased, leading to an increase in the content of hard monomers and functional monomers in the resin system, thus improving cohesive strength. Thermal conductivity and adhesive properties improved simultaneously, making it suitable for heat dissipation and bonding applications in medium-to-high power devices.
[0069] Example 5: The amount of boron nitride modified with boric acid-silica sol was 50% of the mass of the solid component of the acrylic copolymer resin obtained in step S2; the boron nitride sheet diameter was the largest, and the amounts of boric acid and silica sol were the highest. Thermal conductivity reached its highest level, and adhesion performance simultaneously reached its peak, fully meeting the performance requirements of high-power heat dissipation scenarios.
[0070] Comparative Example 1, without the addition of thermally conductive filler, had the lowest thermal conductivity, failing to meet heat dissipation requirements. Its tackiness was lower than in the other examples, and its performance retention after high-temperature aging was insufficient. Comparative Example 2 used unmodified boron nitride as a direct filler. Although its thermal conductivity was improved compared to pure adhesive, it was still far lower than the examples with the same filler content. Furthermore, its peel strength was lower than pure adhesive, and the adhesive film surface showed particle and fogging defects. After high-temperature aging, residual adhesive appeared, and the performance retention rate decreased significantly, indicating poor interfacial compatibility between unmodified boron nitride and the resin matrix, resulting in unsatisfactory thermal conductivity and adhesion.
[0071] The above results demonstrate that the synergistic effect of the BO-Si covalent shell constructed through boric acid-silica sol modification and the BOP coordination bonds constructed from the phosphate groups on the resin side chains creates a strong chemical bond between the filler and the resin matrix. This reduces interfacial thermal resistance and improves interfacial stress transfer efficiency, thereby achieving a synergistic improvement in thermal conductivity and adhesion. The performance gradient changes in Examples 1-5 and the adjustments to process parameters show a clear correspondence, revealing the influence of different process parameters on the structure and performance of the pressure-sensitive adhesive, further confirming the rationality of the process parameter range of this invention.
[0072] The above-disclosed embodiments are merely a few specific examples of the present invention. However, the embodiments of the present invention are not limited thereto, and any variations that can be conceived by those skilled in the art should fall within the protection scope of the present invention.
Claims
1. A method for preparing an interface-synergistic high thermal conductivity acrylic pressure-sensitive adhesive, characterized in that, Includes the following steps: S1. Disperse hexagonal boron nitride in an aqueous boric acid solution, add nano-silica sol, wash, and dry to obtain boric acid-silica sol modified boron nitride; S2. Mix the soft monomer, hard monomer, and functional monomer with phosphate methacrylate to obtain a comonomer, add an initiator to carry out a copolymerization reaction, and obtain an acrylic copolymer resin. S3. The boric acid-silica sol-modified boron nitride obtained in S1 is dispersed in the acrylic copolymer resin obtained in S2. Then, a crosslinking agent is added and stirred to mix. After coating and heat curing, a high thermal conductivity acrylic pressure-sensitive adhesive is obtained.
2. The preparation method of the interface-synergistic high thermal conductivity acrylic pressure-sensitive adhesive as described in claim 1, characterized in that, In step S1, the mass fraction of the boric acid aqueous solution is 5wt% to 15wt%; and the mass of pure boric acid solid added is 10% to 35% of the mass of hexagonal boron nitride.
3. The preparation method of the interface-synergistic high thermal conductivity acrylic pressure-sensitive adhesive as described in claim 1, characterized in that, In step S1, the diameter of the hexagonal boron nitride sheet is 5–20 μm; In step S1, the average particle size of silica in the nano-silica sol is 15-50 nm, and the solid content is 20%-30%. In step S1, the amount of nano-silica sol added is 5% to 20% of the mass of hexagonal boron nitride based on the mass of silicon dioxide.
4. The preparation method of the interface-synergistic high thermal conductivity acrylic pressure-sensitive adhesive as described in claim 1, characterized in that, In step S2, based on a total comonomer mass of 100 parts by mass, the mass parts of each comonomer are: 57-87 parts of soft acrylate monomer, 10-30 parts of hard monomer, 2-8 parts of functional monomer, and 1-6 parts of phosphate methacrylate, with the sum of the four being 100.
5. The preparation method of the interface-synergistic high thermal conductivity acrylic pressure-sensitive adhesive as described in claim 1, characterized in that, In step S2, the acrylate soft monomer is one or more of butyl acrylate, isooctyl acrylate, and ethyl acrylate; The hard monomer is one or more of methyl methacrylate, vinyl acetate, and styrene; The functional monomer is one or more of acrylic acid, methacrylic acid, hydroxyethyl acrylate, and hydroxypropyl acrylate.
6. The preparation method of the interface-synergistic high thermal conductivity acrylic pressure-sensitive adhesive as described in claim 1, characterized in that, In step S2, the initiator is azobisisobutyronitrile or benzoyl peroxide, and the amount of initiator used is 0.3% to 0.9% of the total mass of the comonomer. The copolymerization reaction is carried out in the presence of a solvent, namely ethyl acetate, which accounts for 48% to 65% of the total mass of the comonomer and the solvent. The copolymerization reaction was carried out at a temperature of 70–82°C for 4.5–8 hours.
7. The preparation method of the interface-synergistic high thermal conductivity acrylic pressure-sensitive adhesive as described in claim 1, characterized in that, In step S3, the amount of boric acid-silica sol-modified boron nitride added is 20% to 50% of the mass of the solid component of the acrylic copolymer resin obtained in step S2; The crosslinking agent is an isocyanate crosslinking agent or an epoxy crosslinking agent, and the amount of crosslinking agent used is 0.5% to 2% of the mass of the solid component of the acrylic copolymer resin obtained in step S2.
8. The preparation method of the interface-synergistic high thermal conductivity acrylic pressure-sensitive adhesive as described in claim 1, characterized in that, In step S3, the specific steps of stirring and mixing are as follows: (1) Boric acid-silica sol modified boron nitride and ethyl acetate are mixed at a mass ratio of 1:(1~2) and stirred at 300~500 rpm for 10~15 min to obtain boric acid-silica sol modified boron nitride pre-dispersion slurry; (2) Add the boric acid-silica sol modified boron nitride pre-dispersion slurry to the acrylic copolymer resin in 3 to 5 batches. After each batch is added, stir for 10 to 15 minutes at a speed of 800 to 1200 rpm and a temperature of 40 to 50°C to obtain a mixed slurry. (3) Disperse the mixed slurry under ice-water bath conditions with ultrasonic power of 200-300W for 5-10 minutes, and control the system temperature to not exceed 50℃ during the dispersion process; (4) After ultrasonic treatment, seal the mixed slurry and let it stand at 30-40°C for 30-60 minutes. Then add the crosslinking agent, stir at 200-300 rpm for 5-10 minutes and degas under vacuum. Then it can be coated and cured. In step S3, the thermosetting process employs a three-stage gradient heating process, specifically as follows: Place the coated wet film in an oven at 60-80℃ and bake for 1-2 minutes to complete the interface pre-reaction; then raise the temperature to 100-115℃ and bake for 1-2 minutes; finally, continue to raise the temperature to 120-130℃ and bake for 30-60 seconds; throughout the curing process, control the laminar airflow velocity in the oven to 0.5-1.5 m / s to avoid direct blowing on the adhesive surface, which may cause pinholes and ripple defects.
9. A type of interface-synergistic high thermal conductivity acrylic pressure-sensitive adhesive, characterized in that, It is prepared by the method of any one of claims 1-8 for preparing the interface-synergistic high thermal conductivity acrylic pressure-sensitive adhesive.
10. The application of the interface-synergistic high thermal conductivity acrylic pressure-sensitive adhesive as described in claim 9, characterized in that, This interface-coordinated high thermal conductivity acrylic pressure-sensitive adhesive is used for heat dissipation bonding of power battery components, thermal conductivity of electronic chips and heat sink interfaces, bonding of LED beads and aluminum substrates, and thermal interface assembly of 5G power devices.
